Assessing the genotoxic potential of wastewater effluents from three wastewater treatment plants in South Africa - Rahzia Hendricks; Hein H. Du Preez (IWA Publishing, 2024)
Wastewater treatment plants are mainly monitored for quality in terms of their biological oxygen demand and microbiological constituents as stipulated in the specific discharge permit. Wastewater influents and effluents were taken from three WWTPs in South Africa over the summer and winter seasons. Previous toxicity tests such as the Vibrio fischeri bioluminescence assay and the Selenastrum capricornutum algal growth inhibition test have shown that the effluents displayed acute toxicity. To further investigate the quality of the effluent, the genotoxic potential was determined using the SOS Chromosome and UMU Chromosome test. The SOS Chromotest demonstrated induction factor values of above 1.5 for influents during both seasons indicating that the influents were genotoxic (p < 0.05). Effluents discharged during winter and summer also had induction factors greater than 1.5 (p < 0.05). A range of induction factors was detected with the UMU-Chromotest for influents and effluents (1.98 ± 0.38 and 2.40 ± 0.51, respectively). Findings show point sources in the area can lead to influents and effluents that are potentially genotoxic. Designing a monitoring programme that encompasses testing of both the regulatory determinants with additional specialized tests can provide a more holistic view of wastewater quality and the efficiency of WWTP to reduce the discharge of hazards. HIGHLIGHTS Wastewater treatment plants are unable to remove genotoxic compounds present in effluents.; Wastewater treatment plants are poorly maintained and have failing infrastructure, consequently the discharge of untreated effluents into the environment.; Wastewater treatment plant managers should look at alternative methods of testing other than conventional methods in order to provide a holistic water quality.; The UMU-C test and the SOS Chromotest are relatively easy assays that can be used to determine.; Seasonal differences of the presence of genotoxic compounds in effluents can be seen.;